(untitled) - Coedès, G. (California, 1967)
Contents: The pattern of settlement in Indochina; The founding of the first Indochinese states; The Indochises states from the sixth to the thirteenth century; The crisis of the thirteenth century and the decline of Indian cultural influence; The Indochinese states after the thirteenth century.
Keywords: Asia, Southeastern,Châu Á, Đông Nam Á; History,Lịch sử